Antioxidant Activities and Potential Wound Healing Effects of Meniran (Phyllanthus niruri) Extract Gel - Arif, Julio; Nasution, Ali Napiah; Nasution, Sri Wahyuni; Widowati, Wahyu; Dewi, Nindia Salsabila Mia; Kusuma, Hanna Sari Widya (Folia Medica Indonesiana, 2024)
Highlights: 1. This study analyzed the potential of Meniran extract gel for wound healing therapy, a plant-based medicine that has not been thoroughly researched in the context of promoting a healthy lifestyle. 2. The analysis found that Meniran extract gel has antioxidant properties that can be used for wound treatment to improve human health. Abstract Research on the use of medicinal plants to treat numerous diseases has been widely conducted. However, for chronic wound healing, the availability of medicinal plants for treatment remains rare. Gels containing active plant-based compounds may provide a solution. Phyllanthus niruri, known as